The effect of partial replacement of commercial rabbit pellet with rice sprout on the growth performance and digestibility in rabbits - Naseri, Ahmed Shah Masood (2015)
Rabbit has the advantages of being herbivorous animals, as they can use the protein from the leaves, efficiently convert high fibrous foods, has a fast growth rate and available in variety of breeds. Fodder sprout are one of the feed sources of animal that can be used in feeding of rabbit. There are many advantages using fodder sprout as an animal feed because of their special characteristic such as ease to establishment, good competitive ability, high productivity, require less fertilizer, persistent to local pests and diseases. In addition, the fodder sprout has good nutritive value and reasonable palatability to animals. The objectives of this study were to determine the effect of partial replacement of commercial rabbit pellet with the rice sprout on growth performance and nutrient digestibility. Four treatment diets were formulated to contain rice sprout level of 0%, 20%, 40 % and 60%. Sixteen male weaned rabbits were used for experiment. They were randomly divided into 4 groups of 4 rabbit per treatment, in a Completely Randomized Design (CRD). The rice sprout and commercial rabbit pellet was fed at restricted level. Total feed given were 10% of body weight on dry matter (DM) basis. Analysis of rice sprout on DM basis indicated that it contained 17.68% DM, 5.64% ash, 10% CP, 2.09% EE, 31.55% NDF, 17.59% ADF and 5.56% ADL. The dry matter (DM) and crude protein digestibility were significantly different (p<0.05) while crude fibre (CF) and ether extract (EE) were not significant different (p>0.05). The feed intake and FCR were significantly different compared to control treatment. The body weight gain was not significant different between the treatments. As conclusion, the findings generally indicated that the rice sprout only improve the feed intake and nutrient digestibility in dry matter and crude protein.